Avicennia marina endogenous promoter AMGT1P33 enhances salt tolerance in Arabidopsis by regulating exogenous salt-tolerance genes - Wang, Yi; Jia, Shuwen; Xu, Xinze; Shen, Jie; Zhang, Jian; Cai, Zefu; Chen, Shiquan (Frontiers in Plant Science, 2025)
IntroductionMangroves form ecologically and economically important ecosystems and are a potential source of valuable genetic resources given their natural salt tolerance. However, the role that promoters play in their salt-tolerance mechanisms remains unclear.MethodsIn this study, we identified the AMGT1P33 promoter in the genome of the mangrove tree species Avicennia marina using PromPredict and then verified its promoter function according to the transient expression of GUS. Subsequently, the characteristics of AMGT1P33 and its involvement in salt tolerance were investigated.ResultsAnalysis of the transcription range showed that AMGT1P33 regulates GUS expression in both dicotyledonous (Nicotiana tabacum, Pachyrhizus erosus, and Solanum tuberosum) and monocotyledonous (Agropyron cristatum, Cocos nucifera, and Thalassia hemprichii) plant species. According to quantitative real-time-PCR, the expression level of GUS in N. tabacum when regulated by AMGT1P33 was 5.97 times higher than that when regulated by the 35S promoter. Additionally, the regulation of AmBADH expression by AMGT1P33 in yeast and Arabidopsis significantly improved salt tolerance.DiscussionThese findings suggest that endogenous salt-tolerance-related promoters play a key role in the salt-tolerance mechanism of A. marina. These findings can be extended to elucidate the salt-tolerance mechanisms in other plants and contribute to the development of new promoter tools and methods for transgenic engineering.